STRUCTURING AND THE NOTION "TIME": A GENERAL SEMANTICS CONSCIOUS TIME-BINDING APPROACH. - DAWES, MILTON (ETC: A Review of General Semantics, 2015)
The article focuses on structure and other conscious time-binding evaluating tools under general semantics. It discusses the notions of past, present and future events, the expansion of visual horizons through structural orientation and the importance of order, relationships and interactions to structure. Also mentioned are the structuring of time and space, conscious abstracting and the principle of nonidentity.